2007
DOI: 10.1080/14017430701393218
|View full text |Cite
|
Sign up to set email alerts
|

Low perfusion pressure during CPB may induce cerebral metabolic and ultrastructural changes

Abstract: MAP below 45 mmHg during CPB was associated with cerebral biochemical and morphological changes consistent with anaerobic metabolism and subcellular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Use of off-pump surgery and a no-touch aorta technique in the case of diseased ascending aorta, 28,29 improving CPB techniques and materials, 30 reducing CPB and aorta clamping times, 31 and avoidance of intraoperative hypoperfusion, 32 are measures which may significantly reduce the risk of postoperative CVA.…”
Section: Discussionmentioning
confidence: 99%
“…Use of off-pump surgery and a no-touch aorta technique in the case of diseased ascending aorta, 28,29 improving CPB techniques and materials, 30 reducing CPB and aorta clamping times, 31 and avoidance of intraoperative hypoperfusion, 32 are measures which may significantly reduce the risk of postoperative CVA.…”
Section: Discussionmentioning
confidence: 99%
“…Haugen et al [15], found biochemical and morphologic changes consistent with hypoperfusion and anaerobic metabolism when MAP decreased below 40 mmHg and CPP below 30 mmHg during hypothermic (28°C) cardiopulmonary bypass. In the present study, however, the L/P-ratio remained within normal range.…”
Section: Discussionmentioning
confidence: 99%